Gene Transfer to Rice Mediated by Agrobacterium tumefaciens: Transient Expression of sgfp in Rice Calluses of indica cv. Fatmawati and japonica cv. Nipponbare - Tomohiko Yoshida; Nono Carsono (Zuriat, 2008)
Transient expression of synthetic green fluorescent protein (sgfp) mediated by Agrobacterium is rapid and useful approach for visual monitoring the genetic transformation event in transformed cells/tissues of examined genotype. The significant differences in transient expression of two genotypes (indica cv. Fatmawati and japonica cv. Nipponbare) were found with regard to the osmotic treatment (0.4 M mannitol), solid subcultured callus, and 10 min. air drying. While, no significant differences in sgfp expression were observed in two genotypes on without air-drying and 5 min. air-drying of calluses prior immersed in Agrobacterium suspension. Surprisingly, the sgfp expression could not be detected in suspension-subcultured callus of both cultivars. The highest sgfp expression was achieved in Nipponbare callus treated with 10 min. air drying. The level of green fluorescent spots was higher in Nipponbare than that in Fatmawati, however, plants regenerated from Fatmawati were considerably comparable with those of Nipponbare. Seventeen and 16 putative transgenic rice plants expressing sgfp transgene were obtained from Nipponbare and Fatmawati, respectively.